PENGARUH TEKNIK REBOZO TERHADAP NYERI DAN LAMA PERSALINAN KALA 1 FASE AKTIF - Ita Ayu Agustin (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2023)
Rebozo technique is a birth technique from Latin America which is a non-invasive practice to reduce pain during labor and length of labor. This study aims to determine the effect of the rebozo technique on pain and duration of labor during the first stage of active phase at TPMB Susiani in Banyuwangi Regency in 2023. This research uses a quasi-experimental design with a post test only with control group design approach. The research was conducted in December 2022-January 2023 with a sample size of 20 mothers who met the inclusion and exclusion criteria in each treatment group and control group. Data were collected using a record form which contained the respondents' characteristics and age, gestational age, pre-pregnancy body mass index, parity, education and employment. Research analysis used the Mann Whitney test and unpaired T-test. All respondents in this study have provided informed consent. The research results showed that there was no effect of the rebozo technique on reducing pain (p value=0.931) and length of labor during the first active phase (p value=0.083) for all respondents. This shows that the rebozo technique that has been given to mothers in labor cannot have a significant effect on reducing pain and length of labor during the first stage of active phase.